Heterogeneity and monetary policy: A thematic review - Felipe Alves; Christian Bustamante; Xing Guo; Katya Kartashova; Soyoung Lee; Thomas Pugh; Kurt See; Yaz Terajima; Alexander Ueberfeldt (Bank of Canada, 2022)
The heterogeneity of businesses and households impacts aggregate economic fluctuations and, in turn, is shaped by aggregate fluctuations. This view has emerged over the last decade with strong implications for the transmission and conduct of monetary policy. Our thematic review focuses on key aspects of this new theory as well as its underlying assumptions. We place the insights in a Canadian context using relevant microeconomic and macroeconomic data.
Keywords: D31; E24; E50; E52; D25; E22; 330; Economic models; Monetary policy transmission; Monetary policy and uncertainty